Effects of geometric and operational uncertainties on aerodynamic performance of centrifugal compressor stage. (May 2022) - Zhu, Rui; Ju, Yaping; Zhang, Chuhua
No real centrifugal compressor can exactly conform to its design geometry and expected operating conditions due to the uncertainties existing in the manufacturing and operational processes. Such uncertainties have been increasingly recognised to be detrimental to compressor performance. However, quite few studies have focused on the combined effects of geometric and operational uncertainties on compressor performance, and the underlying flow mechanism even remains unclear. In this context, we here present an uncertainty analysis of a centrifugal compressor stage, with both geometric and operational uncertainties taken into account. With the combination of CFD simulation and nonintrusive sparse grid based stochastic collocation methods, the combined and individual effects of total inlet temperature, total inlet pressure, outlet mass flow, impeller tip clearance and hub fillet radius on the stage/impeller performance are quantified and analysed. Particular attention is paid to elucidating the compressor performance variations through flow field and energy decomposition analyses. Results show that the considered uncertainties exert more influence on the compressor stage performance rather than on the impeller performance. Amongst the examined uncertainties, the impeller tip clearance contributes the most to the stage performance. The underlying mechanism lies in that the wake of impeller tip clearance produces distorted flow downstream towards the diffuser, which causes complicated vortex structures and less conversion of kinetic energy to pressure rise in the diffuser passage. The present study lays a theoretical foundation for the further uncertainty quantification and robust design of centrifugal compressors against various sources of uncertainties.